Sudah Tahu Berbahaya, Tapi Tetap Dibeli? E-Wom dan Pengetahuan Produk dalam Keputusan Pembelian Hand & Body Lotion Dosis Tinggi - Adriani, Rini; Stiadi, Muhamad; Kurniadi, Hanif (Innovative: Journal Of Social Science Research, 2025)
This study analyzes the impact of Electronic Word of Mouth (E-WOM) and product knowledge on the purchase decision of high-dose hand & body lotion on the Facebook platform. Using a quantitative method with questionnaire distribution, this study included 110 respondents selected using purposive sampling. The data were analyzed through Structural Equation Modeling (SEM) using Partial Least Squares (PLS) with Smart PLS. The results indicate that E-WOM and product knowledge have a positive and significant influence on purchase decisions.